Jodorowsky: del cine vanguardista a la escritura psicomágica - David Guzmán Játiva; Erika Granda (Cuadernos LIRICO)
The following article states that psychomagic, Alejandro Jodorowsky's psychotherapeutic invention, is an unexpected, and to some extent unwanted, derivation of his career as a filmmaker. After his successful rise with films like El topo and La montaña sagrada, Jodorowsky suffers a resounding failure with Dune and then a total defeat with Tusk: psychomagic becomes, then, an activity that initially solves his economy and that ends up substituting the cinema as a form of expression.